Langue et mode de production: une esquisse de modèle théorique - Dorais, Louis-Jacques (Anthropologica, 2022)
The point of this paper is to submit for discussion reflexions on the articulation between the linguistic structure and the Marxist model of mode of production. For us, language is a relation between a semi-autonomous syntactic structure and a semantic structure representing some types of social relations of production